Reliability of Diagnosis of Partial Union of Scaphoid Waist Fractures on Computed Tomography - Drijkoningen, Tessa; ten Berg, Paul Willem Louis; Guitton, Thierry G.; Ring, David; Mudgal, Chaitanya S. (Journal of Hand and Microsurgery, 2018)
Computed tomography (CT) is increasingly used not just to diagnose union but also to estimate the percentage of the fracture gap that is bridged by healing bone. This study tested the primary null hypothesis that there is no agreement between observers on the extent of union of a scaphoid waist fracture on CT. CT scans of 13 nondisplaced scaphoid waist fractures treated nonoperatively were rated by 145 observers. CT scans were done 10 to 12 weeks after injury. Observers were asked to “eyeball” measure percentage of union. We found that there was a moderate agreement on the categorical degree of partial union of a scaphoid waist fracture on CT (k = 0.34). Agreement on the location of bony bridging was slight (k = 0.31). We concluded that there is limited reliability of diagnosis of partial union of a scaphoid waist fracture on CT and that this should be taken into account in both patient care and research. This is a Level III, diagnostic study.
Keywords: scaphoid waist fracture; computed tomographic scan; interobserver study; union